RANCANGAN SAKLAR OTOMATIS LAMPU RUANGAN PADA GEDUNG SCIENCE ART MUSIC DI SEKOLAH TINGGI PENERBANGAN INDONESIA - Akbar Subagio; Bachrul Huda; Nurhedhi Desryanto (Langit Biru: Jurnal Ilmiah Aviasi, 2017)
In the area of Indonesian Civil Aviation Institute there is a Science Art Music Building usually used as a entertainment area. The fuction of that building as a entertainment area for cadets in free time. However the operation of the lamp still manual, and many of cadets forget to turn off back the lamp after using the room. Based on the condition nowdays so that I decided to take a design of sakelar automatic lamp based on arduino uno in the science art music building in the Indonesian Civil Aviation Institute. The Carrier System of this design by using microcontroller Arduino and Light Sensor Module as Sensor when cadet entering or coming out from the room. Light Sensor Module will activate Arduino and then automatically activated LCD and Relay. Relay will activate lamp fitting as a spot to activate and extinguished the lamp. By using the design of sakelar automatic lamp will create the lamp room that can turn on and turn off automatically without manual operation when cadet entering or getting out from the room.